Cybersecurity Awareness Mobile Apps for Secondary School Students: LetSecure - Zulkifli, Zahidah; Jafri, Azma Melia; Jamaluddin, Nur' Ain Zulaikha (2021)
LetSecure is one of the mobile applications that can be helpful for internet users to know more about the security of their data and information, and also the types of malware attacks that they can face when using the internet. They also can know ways on how to protect the data from being breached or stolen by the data theft that can lead to misusing it for other things. It also helps the teacher to use the knowledge that they got from the system to teach back to their students. In order to attract secondary school students to become more interested in cybersecurity careers, this mobile application gives them knowledge on what cybersecurity is as a career. This application is a mobile application, that has been developed using Android Studio Code, Node.js, flutter, HTML5, and CSS with the System Development Life Cycle method.